The opera «Dialogues of the carmelites»: Lviv premiere in the light of modèle parisien by Francis Poulenc - Rizaieva, Ganna (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
The relevance of the study. Francis Poulenc’s opera «Dialogues of the Carmelites» is one of the greatest works of the 20th century. Since its premiere at Milan’s La Scala theater in January 1957, it has not left the world’s leading opera stages. At the same time, the composer considered the Paris performance at the Opera Garnier to be la représentation modèle of his second opera, which, in his opinion, perfectly embodied the composer’s idea and the spirit of Bernanos-Poulenc. The Ukrainian premiere of «Dialogues of the Carmelites» on the stage of the Lviv Opera in 2024 revealed the problems of highlighting the basis for Poulenc’s creation of la representation modèle and its main characteristics, raised the issue of the production concept of the Lviv spectacle and the original director’s interpretation of the Poulenc’s opera. The article, for the first time in the Ukrainian musicological space, examines the history of the first, decisive for the future of this opera, productions in Milan and Paris, and also analyzes the production concept of the Lviv «Dialogues of the Carmelites» in the context of Poulenc’s la représentation modèle, which allows to understand deeper both the opera «Dialogues of the Carmelites» itself and the modern trends in the development of the opera theater. The main objective of the study is to identify the specifics of the the production concept of the premiere performance of «Dialogues of the Carmelites» by the Lviv Opera in the context of Poulenc’s parisian la représentation modèle. The research methodology: historical and biographical (in studying the history of the premiere performances of «Dialogues of the Carmelites» in Milan and Paris), comparative and analytical (for a comparative analysis of the production concepts of the Paris and Lviv performances of Poulenc’s second opera). Results and conclusions: Based on letters, interviews of the composer, journalistic materials of the premiere year of «Dialogues of the Carmelites», the process of preparing the opera for the stage version is highlighted, Poulenc’s active participation in the organization of the Paris production, which the composer considered universal la représentation modèle, was revealed. The fundamental differences in the production concept of the opera’s world premiere in 1957 at the Teatro alla Scala in Milan and the Paris production at Garnier l’Opéra are explored. The relevance of the author’s interpretation of the score of Poulenc’s «Dialogues» by the team of directors of the Lviv Opera was revealed: the production strategy was investigated, the strengthening of the idea of the work’s cinematic nature was analyzed through cuts and re-emphasis of the opera’s key dramatic moments. It has been proven that by reemphasizing the deeply religious content of Poulenc’s work into the humanistic plane of human values, by raising the themes of human choice in a topical tragic reality and the manifestation of heroism in it by an ordinary person who suffered from fear and despair «yesterday», adding easily readable allusions to the modern russian-ukrainian war, the Lviv performance brilliantly demonstrated the possibilities of «modern actualized theater».